Trends in Tourism Development in European Union Countries Before and After the COVID-19 Pandemic. How Quickly Has the Global Tourism Industry Recovered? - Cheba, Katarzyna; Bąk, Iwona; Ertmańska, Karolina (Trendy w rozwoju turystyki w krajach Unii Europejskiej przed pandemią Covid-19 i po niej. Jak szybko globalna branża turystyczna odzyskała równowagę?, 2025)
Aim: The purpose of the article was to determine the development trends of tourism before and after the COVID-19 pandemic and to try to answer the question: How quickly did the tourism industry recover in EU countries and return to its pre-pandemic state? Methodology: Two research approaches were used to build forecasts of selected tourism intensity indicators. The first one uses the trend models with seasonal fluctuations estimated based on monthly data before the pandemic. The forecasts were revised considering the current situation in the tourism market in individual EU countries. Various dynamics measures were used to estimate the value of the adjustment factor. As part of the second research approach, the Holt-Winters adaptive models were used. Results: The analysis showed that EU countries have coped with the pandemic to varying degrees. Some of them, such as those in Southern Europe, recovered to pre-pandemic levels of tourism market activity relatively quickly. Surprisingly, this did not apply equally to all countries in the region (e.g. Italy). Implications and recommendations: The research results described can be helpful for researchers and practitioners, such as government agencies and private companies, to review the forecasts and their application in forecasting tourism demand. Originality/value: The added value of the work was the original research approach used by the authors, combining various statistical and econometric methods to predict the direction and rate of the recovery of the global tourism industry.
Econometrics = Ekonometria, 2025, Vol. 29, No. 4, s. 1-17
Keywords: tourism intensity indicators; COVID-19 pandemic; EU countries trend models; adaptive models; wskaźniki intensywności ruchy turystycznego; COVID-19; kraje UE; modele trendów; modele adaptacyjne